Foreign Policy Concept of the Republic of Kazakhstan: Cooperation with U.S. (International relations and international law Journal, 2016)
In January of the current year was published the Foreign Policy Concept of Kazakhstan for 2014-2020., which contains the fundamental goals and objectives of the priority directions and mechanisms of their solution.Published document provides answers to the questions under discussion actively in the academic peer environment. The Foreign Policy Concept of the Republic of Kazakhstan 2014-2020 periodidentified by country and regional priorities. Relations with the U.S. are characterized as a strategic partnership aimed at the development of political, trade-economic, investment, energy, scientific-technical and humanitarian cooperation, the solution of pressing issues on the international agenda. The United States, despite the presence of the geopolitical and economic interests, has not worked out a Central Asia strategy. Deepening strategic cooperation will promote the political dialogue at the highes level in the format of a regional dialogue with 5 +1(Central Asia + USA) at the level of State Secretary and Minister of Foreign Affairs, in addition to the existing bilateral mechanisms
Keywords: concept; multi-vector foreign policy; the strategic partnership; Kazakhstan; USA